2012
DOI: 10.1007/s10552-012-0034-7
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal characteristics and retinoblastoma

Abstract: Purpose The etiology of retinoblastoma remains poorly understood. In the present study, we examined associations between perinatal factors and retinoblastoma risk in California children. Methods We identified 609 retinoblastoma cases (420 unilateral, 187 bilateral, and 2 with laterality unknown) from California Cancer Registry records of diagnoses 1988–2007 among children <6 years of age. We randomly selected 209,051 controls from California birthrolls. The source of most study data was birth certificates. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 58 publications
5
51
1
Order By: Relevance
“…As this was a record-based study, we did not seek informed consent from individual subjects. The demographic and gestational characteristics of cases and controls have been previously reported (Abrahao et al, 2015; Hall et al, 2016; Heck et al, 2012; Heck et al, 2013b; Heck et al, 2014, 2015; Heck et al, 2013c; Shrestha et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…As this was a record-based study, we did not seek informed consent from individual subjects. The demographic and gestational characteristics of cases and controls have been previously reported (Abrahao et al, 2015; Hall et al, 2016; Heck et al, 2012; Heck et al, 2013b; Heck et al, 2014, 2015; Heck et al, 2013c; Shrestha et al, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Choice of potential confounders was guided by our prior work on retinoblastoma, 16 with all confounding factor information taken from birth certificates. We adjusted for maternal race/ethnicity and nativity (White non-Hispanic, Hispanic and US-born, Hispanic and foreign-born, other race/not specified), paternal age (<29, 30–34, 35+), and year of birth.…”
Section: Methodsmentioning
confidence: 99%
“…In a large population based case-control study of childhood cancer in California we conducted previously, we found elevated odds for unilateral retinoblastoma among children of U.S.-born Hispanic women and decreased odds among children of mothers born in Mexico (8). We also observed elevated odds in infants born to mothers exposed to higher levels of traffic related air pollution during pregnancy (911).…”
Section: Introductionmentioning
confidence: 80%